Effects of volatile–char interactions on in-situ destruction of nascent tar during the pyrolysis and gasification of biomass. Part II. Roles of steam - Song, Yao; Wang, Yi; Hu, Xun; Xiang, J.; Song, H.; Mourant, Daniel; Li, Tingting; Wu, Liping; Li, Chun-Zhu (Elsevier Ltd, 2015)
This study aims to investigate the importance of steam to tar destruction during the volatile–char interactions. Steam was supplied in the absence and presence of nascent char during the pyrolysis/gasification of biomass at 850 C. In the absence of char, steam has more significant effects on the reforming of large aromatic ring systems (e.g. >2 fused benzene rings) than small and isolated aromatics. In the presence of char, steam can significantly enhance the reforming of both large and small aromatic ring systems during the volatile–char interactions, especially when the steam–char reactions are also significant. The results indicate that the steam–char reactions are particularly inhibited in a thin char bed by the volatile–char interactions. It is believed that the steam–char reactions can produce additional active sties on the char, such as the radicals/intermediates of char gasification and/or the O-containing groups, to facilitate tarreforming during the volatile–char interactions.